UPAYA MENINGKATKAN KEMAMPUAN PASSING DAN STOPPING SEPAK BOLA MELALUI METODE DEMOSNTRASI PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA - Marwansyah, Geostaril; Apriani, Leni; Alpen, Joni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The aim of this research is to see the improvement of football passing and stopping abilities through the demonstration method in class VII.6 students at SMP Negeri 6 Siak Hulu. The problem is that there are still many students whose mastery of passing and stopping techniques is not optimal. When kicking the ball, players should look at the friend where the ball will be passed or kicked. Many students kick the ball incorrectly towards the target. Incorrect body position. When kicking, the ball should be aimed straight forward with the ankle bent inward. Students often kick the ball with the instep, toe. Then when stopping the ball (stopping) the students were not able to control the ball well. The type of research is classroom action research. The test used in this research uses PTK which presents an assessment rubric in two cycles regarding passing and stopping in a soccer game. The research subjects in this study were 25 students in class VII.6 of SMP Negeri 6 Siak Hulu. From the results found in the field, in cycle I it was found that 19 people or 76% had passed the KKM and 6 people had not passed the KKM, while in cycle II it was found that 25 people or 100% had passed the KKM and 0 people had not passed. KKM.